2019
DOI: 10.3390/cells8101174
|View full text |Cite
|
Sign up to set email alerts
|

Syncytiotrophoblast of Placentae from Women with Zika Virus Infection Has Altered Tight Junction Protein Expression and Increased Paracellular Permeability

Abstract: The cytotrophoblast of human placenta transitions into an outer multinucleated syncytiotrophoblast (STB) layer that covers chorionic villi which are in contact with maternal blood in the intervillous space. During pregnancy, the Zika virus (ZIKV) poses a serious prenatal threat. STB cells are resistant to ZIKV infections, yet placental cells within the mesenchyme of chorionic villi are targets of ZIKV infection. We seek to determine whether ZIKV can open the paracellular pathway of STB cells. This route is reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 68 publications
0
37
1
2
Order By: Relevance
“…Histological evaluations of the placenta and umbilical cord shed further light on the maternal‐fetal response to viral infections 28 . Placental trophoblastic apoptosis and vascular damage contribute to increased permeability of the placenta 118 . In SARS‐CoV‐1, during the acute phase, maternal hypoxia may have caused maternal placental blood flow disturbances leading to increased subchorionic or intervillous fibrin deposition; whilst during the convalescent phase, extensive fetal thrombotic vasculopathy with avascular fibrotic villi was observed.…”
Section: What Do We Know About Mother‐to‐child‐transmission Of Sars‐cmentioning
confidence: 99%
“…Histological evaluations of the placenta and umbilical cord shed further light on the maternal‐fetal response to viral infections 28 . Placental trophoblastic apoptosis and vascular damage contribute to increased permeability of the placenta 118 . In SARS‐CoV‐1, during the acute phase, maternal hypoxia may have caused maternal placental blood flow disturbances leading to increased subchorionic or intervillous fibrin deposition; whilst during the convalescent phase, extensive fetal thrombotic vasculopathy with avascular fibrotic villi was observed.…”
Section: What Do We Know About Mother‐to‐child‐transmission Of Sars‐cmentioning
confidence: 99%
“…The permeability of the TJ present in the superficial cells of the multi-stratified epithelium of the cervix of mice was evaluated using the paracellular pathway marker ruthenium red, as previously reported (34,35). Thus, if the ruthenium red stain only highlighted the apical surface of the superficial cells in the cervix, this indicated that passage through the paracellular pathway was blocked due to TJ sealing.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 95%
“…Despite some knowledge regarding ZIKV pathogenesis, its mechanism of infection in placental immune cell types remains limited (116)(117)(118)(119). Histopathology of ZIKV infected placentae has shown ZIKV infection in first trimester villous stromal tissue cells, which includes immune cells in the chorionic villi (117,120,121). Uniquely, ZIKV was also found to infect CTBs, endothelial cells, fibroblasts and HC in chorionic villi, as well as amniotic epithelial cells and trophoblast progenitor cells (103,(116)(117)(118)(122)(123)(124) (Figure 4).…”
Section: Zikvmentioning
confidence: 99%